The youth mental health crisis: analysis and solutions - McGorry, Patrick; Gunasiri, Hasini; Mei, Cristina; Rice, Simon; Gao, Caroline X. (Frontiers in Psychiatry, 2025)
BackgroundSince the mid-20th century, mental illness has become a leading cause of health burden, particularly among adolescents and emerging adults, with most disorders emerging before the age of 25. Over the past two decades, mental ill health has surged to alarming levels, with evidence confirming that the increase is not just due to better awareness or diagnosis but reflects a genuine public health crisis.Study design/methodWe explore the evolving landscape of youth mental health and its contributing factors, including family dynamics, educational pressures, climate change, social media, and socio-economic challenges, potentially linked to neoliberal policies. A narrative review methodology was employed to analyze these factors and their role in the trends of mental ill-health among young people.Study resultsWe document mental health trends since the mid-1990s, focusing on mental and substance use disorders among young people and their current needs. Potential new explanatory factors and megatrends, potentially flowing from a paradigm shift in the global political economy which has largely passed under the radar, yet which has produced fragmentation and inequality, are identified, with the COVID-19 pandemic further intensifying these trends. We discuss methodologies to estimate the contribution of these megatrends and outline potential barriers to implementation, along with strategies to overcome them.ConclusionThis review calls for a comprehensive global action plan, emphasizing prevention, early intervention, and improved treatment strategies. In addition to strengthening prevention, which may take time and be elusive, immediate action is needed to innovate and expand services, which are currently under-resourced and overwhelmed.